Narrative Devices of Ego Erasure: Examining the Phrase “the Beloved Disciple” through Narrative Criticism and Grammatical Analysis in the Gospel of John - Martua Parluhutan Tamba (International Journal of Sociology of Religion, 2026)
The use of the phrase “the beloved disciple” as an anonymous marker in the Gospel of John is often interpreted by some modern critics as a claim of spiritual superiority over other apostles. However, differing interpretations of this narrative motif have created a significant academic gap in understanding the text’s authority. This qualitative study aims to re-examine the theological motive behind the use of this phrase and to demonstrate that the narrative represents humility rather than elitism. The method employed is narrative criticism combined with grammatical analysis of Koine Greek in the Gospel of John. The findings indicate that the author’s anonymity functions as a strategy of ego effacement, transforming a historical figure into the ideal disciple. Textually, the use of the imperfect active indicative verb construction emphasizes that Jesus is the sole active subject in this relationship, meaning that the identity of “the beloved disciple” is entirely grounded in divine initiative rather than personal merit. Furthermore, the comparison with Peter is not intended to assert superiority, but to emphasize that leadership authority should be rooted in relational dynamics rather than mere hierarchy. Thus, the phrase operates as a narrative device of humility, offering an inclusive and service-oriented paradigm of Christian leadership.